Brick-walled cooler - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A back evaporative cooler for storage of fresh produce, with a capacity of 182m3, has been constructed and tested in Kano, Nigeria. The successful storage of produce in the tropics requires cheap structures or containers which reduce ambient...